Improving lecturer competence through SAP training to support technology-based learning processes - Yongky Rangga Yuda Nugraha; Agus Maulana; Andy Setiawan (PT WIM Solusi Prima, 2026)
The rapid advancement of information technology demands that lecturers develop adaptive skills to implement integrated digital learning systems aligned with industry practices. SAP (Systems, Applications, and Products in Data Processing) is an Enterprise Resource Planning (ERP) software widely adopted in various business sectors and increasingly utilized in higher education. Through this community service program, lecturers received intensive training to understand core concepts, operate key SAP modules, and integrate them into technology-based teaching processes. The program was conducted through several stages: preparation, planning, hands-on training, and evaluation. The results showed a significant improvement in lecturers’ competence in understanding the operational flow of the SAP system and their readiness to apply it in teaching activities. This initiative supports the development of innovative, industry-relevant, and technology-driven learning that enhances digital literacy and pedagogical transformation in higher education.